AndroProf: A Profiling Tool for the Android Platform - Sartor, Anderson Luiz; Corrêa, Ulisses Brisolara; Beck Filho, Antônio Carlos Schneider (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2013: Anais do III Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2013)
Current tools for mobile development are very limited in which and how much information they can trace or profile. They are also scarce when compared to general-purpose development tools. This makes the development of embedded applications, with its hard constraints, such as limited performance and power budget, a hard task to be accomplished. Therefore, a tool that provides information such as energy consumption, execution time and other statistics is mandatory when it comes to develop embedded applications. This paper presents a tool that provides the aforementioned information per application and that is able to trace both Dalvik Virtual Machine and native code. To accomplish this, we extended Android SDK's QEMU, and we developed graphical user interfaces to process the traced data.